INTEGRATED MANAGEMENT OF Conotrachelus dubiae IN RELATION TO FRUIT RETENTION OF Myrciaria dubia (CAMU-CAMU) IN A FLOODED AREA, IN LORETO-PERU - PARISI, Irene Luce (2022)
Myrciaria dubia (camu-camu) is an Amazonian fruit of economic importance.The most common problems are the damage caused by Conotrachelus dubiae and the drop of developing fruits. The objective was to clarify the factors influencing post-defoliation fruit retention influenced by C. dubiae in flooded areas. Four treatments were applied: control (T1), bottle trap (T2), adhesive tape trap (T3), and foliar fertilization (T4). The research was conducted at a camu-camu plot on the Amazon River banks. As an additional control, plants at a highland plot were evaluated. Data on the retention of flowers and fruits, yield, and quality were obtained. The presence of pests was monitored, and fruits attacked by C. dubiae were harvested. T2 showed the highest levels of damaged fruit (11.9% ± 9) and fruit retention (24.5% ± 21). This supports the hypothesis that the primary cause of fruit drop is not pest damage. In fact, T4 was the most effective pest control (damaged fruits: 4.1% ± 4). The critical period for fruit retention was right after the fruit set. Defoliation did not have any effects on fruit quality.  Flowering induction, unusually occurring during the flooding period, explains the high stress that caused low fruit retention.